Accelerated waning of immune responses to a third COVID-19 vaccination in patients with immune-mediated inflammatory diseases. Issue 135 (February 2023) - Mrak, Daniel; Kartnig, Felix; Sieghart, Daniela; Simader, Elisabeth; Radner, Helga; Mandl, Peter; Göschl, Lisa; Hofer, Philipp; Deimel, Thomas; Gessl, Irina; Kain, Renate; Winkler, Stefan; et al.
Abstract: Background: A 3 rd COVID-19 vaccination is currently recommended for patients under immunosuppression. However, a fast decline of antibodies against the SARS-CoV-2 receptor-binding domain (RBD) of the spike protein has been observed. Currently it remains unclear whether immunosuppressive therapy affects kinetics of humoral and cellular immune responses. Methods: 50 patients under immunosuppression and 42 healthy controls (HCs) received a 3 rd dose of an mRNA-based vaccine and were monitored over a 12-weeks period. Humoral immune response was assessed 4 and 12 weeks after 3 rd dose. Antibodies were quantified using the Elecsys Anti-SARS-CoV-2 Spike immunoassay against the receptor-binding domain (RBD) of the spike protein. SARS-CoV-2-specific T cell responses were quantified by IFN-γ ELISpot assays. Adverse events, including SARS-CoV-2 infections, were monitored over a 12-week period. Results: At week 12, reduced anti-RBD antibody levels were observed in IMID patients as compared to HCs (median antibody level 5345 BAU/ml [1781–10, 208] versus 9650 BAU/ml [6633–16, 050], p < 0.001). Reduction in relative antibody levels was significantly higher in IMID patients as compared to HCs at week 12 (p < 0.001). Lowest anti-RBD antibody levels were detected in IMID patients who received biological disease-modifying anti-rheumatic drugs (DMARDs) or a combination therapy with conventional synthetic and biological DMARDs. Number of SARS-CoV-2-specific T cells against wildtype and Omicron variants remained stable over 12 weeks in IMID patients. No serious adverse events were reported. Conclusion: Due to a fast decline in anti-RBD antibodies in IMID patients an early 4 th vaccination should be considered in this vulnerable group of patients. Highlights: · Rapid decline of anti-RBD antibodies is observed in immunosuppressed patients after 3 rd COVID-19 vaccination Treatment with biological anti-rheumatic drugs or combination therapy is associated with waning of anti-RBD antibodies ·Cellular immune response is maintained in patients over a 12-weeks period